2018
DOI: 10.3758/s13415-018-0606-4
|View full text |Cite
|
Sign up to set email alerts
|

Flow experience and the mobilization of attentional resources

Abstract: The present study attempts to better identify the neurophysiological changes occurring during flow experience and how this can be related to the mobilization of attentional resources. Self-reports of flow (using a flow feelings scale) and attention (using thought probes), autonomic activity (heart rate, heart rate variability, and breathing rate), and cerebral oxygenation (using near-infrared spectroscopy) in two regions of the frontoparietal attention network (right lateral frontal cortex and right inferior p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
56
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(63 citation statements)
references
References 63 publications
5
56
2
Order By: Relevance
“…Moreover, previous neurofunctional studies found increased frontal brain activation during game-based task versions with higher flow experience [28,32,86]. Using NIRS, de Sampaio Barros et al (2018) investigated neuronal correlates of flow experience during gaming. They found that oxy-Hb was highest in an optimal state of task demands experienced to balance player resources.…”
Section: Plos Onementioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, previous neurofunctional studies found increased frontal brain activation during game-based task versions with higher flow experience [28,32,86]. Using NIRS, de Sampaio Barros et al (2018) investigated neuronal correlates of flow experience during gaming. They found that oxy-Hb was highest in an optimal state of task demands experienced to balance player resources.…”
Section: Plos Onementioning
confidence: 99%
“…Some studies reported a global decrease of oxy-Hb over frontal brain areas during gaming [23][24][25][26][27]. However, differences in task complexity, cognitive load, expertise, or subjective user experience during playing may have added to these different brain activation patterns [28][29][30][31][32].…”
Section: Introductionmentioning
confidence: 99%
“…Considering the involvement of VLPFC in top-down attention (Raz & Buhle, 2006), one can interpret this as a co-activation of the attentional and reward networks during the flow experience (Weber, Huskey, & Craighead, 2016). The results of the study by De Sampaio Barros et al (2018) showed a significant positive correlation between the self-reported measure of attention and the average neural activation in the frontoparietal regions. Higher activation in the lateral PFC was reported in the flow and autonomy conditions while playing Tetris and Pong compared to the other conditions.…”
Section: Synchronization Of Attentional and Reward Networkmentioning
confidence: 92%
“…The observed higher mental effort (lower HRV) and more focused attention (more focused eye gaze) along with less self-reported subjective effort in the flow condition than in the over-challenged condition suggested that the experience of flow is based on an efficient, but effortful, engagement of attention. The link between attention and flow was also examined by De Sampaio Barros et al (2018) to see whether flow mobilizes attentional resources while playing two video games, Tetris and Pong. The authors added an "autonomy" condition to the traditional under-challenged, flow, and over-challenged conditions.…”
Section: Effortless or Effortful Attentionmentioning
confidence: 99%
“…When this happens in the realm of science, fierce debate usually ensues in an attempt to resolve the conflict. An example of this can be found in the field of abnormal Flow Short Scale (Rheinberg et al, 2003) and related scales 2 Baumann et al, 2016Barros et al, 2018Brom et al, 2017Harris et al, 2017a,b Hermann and Vollmeyer, 2016Schattke et al, 2014 Four items from the absorption subscale of the Flow Short Scale Rivkin et al, 2018 Continuous No No Flow Short Scale with three additional items measuring "autotelic experience" Rankin et al, 2019 Continuous Yes Yes (partly) Flow State Scale (Jackson and Marsh, 1996) and related scales Borovay et al, 2019Beltrán et al, 2018Forkosh and Drake, 2017Harmat et al, 2015Joo et al, 2015Kaye et al, 2018Marston et al, 2016 Continuous Yes Yes (partly)…”
Section: The Three Issuesmentioning
confidence: 98%